Association Between Vitamin D Receptor rs731236 (Taq1) Polymorphism and Risk for Restless Legs Syndrome in the Spanish Caucasian Population. Issue 47 (November 2015) - Jiménez-Jiménez, Félix Javier; García-Martín, Elena; Alonso-Navarro, Hortensia; Martínez, Carmen; Zurdo, Martín; Turpín-Fenoll, Laura; Millán-Pascual, Jorge; Adeva-Bartolomé, Teresa; Cubo, Esther; Navacerrada, Francisco; Rojo-Sebastián, Ana; Rubio, Lluisa; et al.
Abstract : Abstract: Several recent works suggest a possible role of vitamin D deficiency in the etiology or restless legs syndrome (RLS). We analyzed the possible relationship of 2 common single nucleotide polymorphisms (SNPs) in the vitamin D3 receptor ( VDR ) gene with the risk for RLS. We studied the genotype and allelic variant frequencies of VDR rs2228570 and VDR rs731236 SNPs in 205 RLS patients and 445 healthy controls using a TaqMan essay. The frequencies of the rs731236AA genotype and the allelic variant rs731236A were significantly lower in RLS patients than in controls ( P < 0.005 and < 0.01, respectively). Restless legs syndrome patients carrying the allelic variant rs731236G had an earlier age at onset, and those carrying the rs731236GG genotype had higher severity of RLS, although these data disappeared after multivariate analyses. None of the SNPs studied was related with the positivity of family history of RLS. These results suggest a modest, but significant association between VDR rs731236 SNP and the risk for RLS.